Pembuatan Bakso Ikan yang Sehat dan Lezat untuk Meningkatkan Keterampilan Masyarakat di Kelurahan Watumotobe Kecamatan Kapontori - Badaruddin, Rusli; Saili, Takdir; Sandiah, Natsir; Bahtiar, Bahtiar; Kimestri, Asma Bio; Putri, Anindyaningrum Zainal; Ilahude, Meygi Caesarika Putri; Hakim, Muh. Haidir (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the skills and knowledge of the community in processing fishery products into processed products with economic value, especially fish balls. The activity was carried out in Watumotobe Village, Kapontori District, with the main target of housewives, MSME players, and fishermen groups. The methods used were counseling, hands-on training in making fish balls, and discussion and evaluation with participants. The results of the activity showed that participants were able to understand and practice the process of making fish balls well, starting from the selection of ingredients, mixing dough, shaping, to boiling and storage techniques. In addition, this activity opened participants' insights about the potential of local fish-based businesses and the importance of product packaging and marketing. The conclusion of this activity is that the fish meatball making training is effective in improving community skills and has the potential to support local economic development based on fishery resources.